Genetic Variability of the Vitamin D Receptor Affects Susceptibility to Parkinson’s Disease and Dopaminergic Treatment Adverse Events - Redenšek, Sara; Kristanc, Tilen; Blagus, Tanja; Trošt, Maja; Dolžan, Vita (Frontiers in Aging Neuroscience, 2022)
Vitamin D is a lipid-soluble molecule and an important transcriptional regulator in many tissues and organs, including the brain. Its role has been demonstrated also in Parkinson’s disease (PD) pathogenesis. Vitamin D receptor (VDR) is responsible for the initiation of vitamin D signalling cascade. The aim of this study was to assess the associations of VDR genetic variability with PD risk and different PD-related phenotypes. We genotyped 231 well characterized PD patients and 161 healthy blood donors for six VDR single nucleotide polymorphisms, namely rs739837, rs4516035, rs11568820, rs731236, rs2228570, and rs1544410. We observed that the VDR rs2228570 is associated with PD risk (p<0.001). Additionally, we observed associations of specific VDR genotypes with adverse events of dopaminergic treatment. VDR rs1544410 (GG vs. GA+AA: p=0.005; GG vs. GA: p=0.009) was associated with the occurrence of visual hallucinations and VDR rs739837 (TT vs. GG: p=0.036), rs731236 (TT vs. TC+CC: p=0.011; TT vs. TC: p=0.028; TT vs. CC: p=0.035), and rs1544410 (GG vs. GA: p=0.014) with the occurrence of orthostatic hypotension. We believe that the present study may support personalized approach to PD treatment, especially in terms of monitoring vitamin D level and vitamin D supplementation in patients with high risk VDR genotypes.